'It's a Hard Balance to Find': The Perspectives of Youth Justice Practitioners in England on the Place of 'Risk' in an Emerging 'Child-First' World. (April 2023) - Day, Anne-Marie
In recent years, there has been a shift in youth justice central policy narratives in England and Wales away from risk assessment and management and towards child first. However, this shift is meeting with a number of challenges on the ground. The reasons for this have been conceptualised as resistance and reticence, contradiction and bifurcation and confusion about competing narratives emerging from different UK government departments about how to meet the statutory requirement to 'prevent' youth offending. The article emphasises the importance of meaningfully engaging with youth justice practitioners in debates about how to meet this challenge.